UROGENITAL CHLAMYDIOSIS: CURRENT STATE (REVIEW) - T. A. Volodina; P. V. Saskova; E. V. Ivanova (Фармация и фармакология (Пятигорск))
Today, infectious diseases of urogenital tract are the reason of the whole range of pathological states. Despite the successes of scientific society in the development of contemporary methods for diagnosis and treatment of sexually transmissive infections their prevalence rate is still high. The review covers the most frequent bacterial sexually transmissive infection chlamydiosis, its prevalence rate and treatment methods